2017
DOI: 10.1111/1541-4337.12295
|View full text |Cite
|
Sign up to set email alerts
|

Developments and Challenges in Online NIR Spectroscopy for Meat Processing

Abstract: Meat and meat products are popular foods due to their balanced nutritional nature and their availability in a variety of forms. In recent years, due to an increase in the consumer awareness regarding product quality and authenticity of food, rapid and effective quality control systems have been sought by meat industries. Near-Infrared (NIR) spectroscopy has been identified as a fast and cost-effective tool for estimating various meat quality parameters as well as detecting adulteration. This review focusses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 89 publications
(134 reference statements)
1
35
0
2
Order By: Relevance
“…The comparison of these findings with the raw spectra shown in Figure 2 confirms the significant role of reflectance bands in the range 570-700 nm and 700-970 nm for the development of PLS-R models [38,68]. As mentioned above, absorption bands at NIR region of 910 nm seemed to be associated with proteins, which are in abundance in chicken meat, especially in chicken breast [61].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The comparison of these findings with the raw spectra shown in Figure 2 confirms the significant role of reflectance bands in the range 570-700 nm and 700-970 nm for the development of PLS-R models [38,68]. As mentioned above, absorption bands at NIR region of 910 nm seemed to be associated with proteins, which are in abundance in chicken meat, especially in chicken breast [61].…”
Section: Discussionsupporting
confidence: 74%
“…More specifically, reflectance at 570-700 nm is related to respiratory pigments such as myoglobin (570 nm), oxymyoglobin (590 nm) and metmyoglobin (630 nm) [23,24,59]. In the NIR region, absorption bands at 910 nm are linked to denaturation of proteins [60,64] while at 750 and 970 nm, O-H second overtones are related to the moisture content in the samples [26,38,53]. In addition, absorption bands observed in the NIR region (928 and 940 nm) are correlated to the presence of fatty acids and fat within the sample matrix [14,60,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of the NIR spectra can be performed using mathematical models and multivariate analysis (chemometrics). Chemometrics utilizes various multivariate techniques, such as principal component regression (PCR) and partial least squares (PLS), in order to build models with the use of reference chemical data obtained through other analytical techniques 29 . However, in the case of the high non-linearity, the mentioned techniques lead to substantial errors.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of the NIR technique to the evaluation of meat quality have been reviewed. (23) The NIR technique has the potential of detecting meat adulteration, (24,25) assessing meat microbial spoilage, (26,27) and estimating meat quality. (28,29) Nowadays, several research studies on Japanese wagyu beef have shown that NIR spectroscopy can be applied to predict the fat content and quantify the fatty acid composition.…”
mentioning
confidence: 99%